Application of pressure programmed absorption and desorption to characterize hydriding and dehydriding kinetics of LaNi5 during activation - Fuster, Valeria de Los Angeles (2007)
Hydriding and dehydriding kinetics is an important aspect of the reaction of hydrogen with different hydride forming materials. In particular, it is a key factor in several applications of hydrogen from an energetic point of view. We present here the use of a recently developed technique to characterize hydrogen absorption and desorption kinetics: pressure programmed absorption and desorption (PPAD). The technique is based on an isothermal pressure-ramped measurement of the hydriding and dehydriding rate, and its principal advantages are the absence of an initial blind period, the short time required to complete an experimental run, and the possibility to automatically perform consecutive hydrogen absorption and desorption cycles. To illustrate this, we present the use of PPAD to follow the evolution of hydriding and dehydriding kinetics of LaNi5 during the activation process. Additionally, we analyze the effect of using hydrogen with different purity levels.